(untitled) (Communications in Mathematical Research, 2021)
This paper is concerned with the electromagnetic scattering by a non-perfectly conductor obstacle in chiral environment. A two-dimensional mathematical model is established. The existence and uniqueness of the problem are discussed by potential theory.